Flexible ureteroscopic renal stone extraction during laparoscopic ureterolithotomy in patients with large upper ureteral stone and small renal stones - Kim, Myung Ki; You, Jae Hyung; Kim, Young Gon (Canadian Urological Association Journal, 2014)
Introduction: We describe laparoscopic ureterolithotomy with renal stone extraction using a stone basket under flexible ureteroscopy. We describe its efficacy through a laparoscopic port and a ureterotomy site in patients with large upper ureteral stone and small renal stones. Methods: Between January 2009 and February 2012, we performed laparoscopic ureterolithotomy with renal stone extraction using a stone basket under flexible ureteroscopy in 11 patients who had upper ureteral and renal stones. The retroperitoneal approaches were used in all patients using 3-4 trocars. Results: All procedures were performed successfully without significant complications. Mean operative time was 78.5 minutes (range: 52-114 minutes). The mean size of ureteral stone was 19.91 mm (range: 15-25 mm). In addition, 25 renal stones (mean size 7.48 mm, range: 2-12 mm) were removed from 11 patients. The mean length of hospital stay was 3.5 days (range: 2-6 days). Conclusions: Laparoscopic ureterolithotomy with renal stone extraction using a stone basket under flexible ureteroscopy can be considered one of treatment modalities for patients with large upper ureteral stones accompanied by renal stones who are indicated in laparoscopic ureterolithotomy.